(untitled) (Journal of the Bangladesh Agricultural University, 2019)
This study was conducted to analyze the profitability of rice farming in Bangladesh. In doing so, it utilized the multistage sampling technique to collect the cross-sectional data from seven rice producing districts in Bangladesh during 2016. A total of 140 samples were directly interviewed using a structured questionnaire for achieving the purpose. Apart from the descriptive analysis of the socioeconomic variables of the selected respondents, the benefit-cost and functional profitability analysis of rice were also performed. The log-linear form of Cobb-Douglas production function was chosen to determine the effects of various inputs on the profitability of rice. The finding of cost-benefit analysis reveals that rice farming is a profitable activity in Bangladesh as the estimated cost of production was lower than the return in the selected study areas. However, the profitability differs among different farmers’ group and large farmers are more profitable in rice cultivation than small and medium farmers. In addition, the functional analysis identifies three inputs such as the cost of power tiller, fertilizer and hired labor as the significant determinants of profitability for all farmers in the study regions. Moreover, these factors also differ across the farmer’s groups except the cost of fertilizer. Therefore, it is recommended in this study that the concerned authority of the government should ensure adequate and timely fertilizer use at a subsidized price which would be affordable by the farmers. Besides, a fair pricing policy should be set so that fluctuation in the price level can be controlled. Effective extension service may also help the farmers using a better combination of input that will generate higher productivity and return, thereby, will contribute to being food secure and self-sufficient in rice cultivation. J. Bangladesh Agril. Univ. 17(1): 86–91, March 2019